(untitled) (Communications in Computational Physics, 2018)
We describe a relativistic semi-Lagrangian scheme for the numerical solution of the relativistic Vlasov-Maxwell system. The implementation strategy on a modern non-unified memory access (NUMA) architecture using the OpenMP framework is discussed. We demonstrated that close to perfect scaling can be obtained on modern many-core, multi-socket systems. Application of this code to the problem of relativistic generation of high-harmonic laser radiation is demonstrated. The results are compared to particle-in-cell (PIC) simulations, indicating in particular that for warm plasma the Vlasov simulation is superior. We discuss the impact of plasma temperature on the radiation spectrum and show that the efficiency of harmonic generation depends on the plasma temperature.